Permanent Studies for Equality and Social Justice as Mission of University Education - Beresnevičienė, Danguolė (Acta Paedagogica Vilnensia, 2001)
This article focuses on the importance of the permanent studies which could be considered as one of the most comprehensive functions of modern universities. Altogether it involves implementation of new informational technologies which may have some advantages or cause some new problems. These questions are revealed on the ground of studies of the new pedagogical and psychological literature, theoretical modelling and the methods of experts. It allowed to discuss some aspects of the changing role of the professors and students and to define the structure of permanent university tudies.
Keywords: Higher education; university; permanent studies; equality; social justice.